UNSUR PEMBENTUK FRASA EKSOSENTRIS DALAM HIKAYAT HANG TUAH - Kartika Bintari; Sumarlam Sumarlam (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
Exocentric Phrase Forming Elements in Hikayat Hang Tuah. The purpose of this study was to describe the exocentric phrase forming elements in Hikayat Hang Tuah. This type of research is descriptive qualitative with the object of research in the form of phrases in Hikayat Hang Tuah. The data in this study are sentences containing exocentric phrases from data sources in the form of Hikayat Hang Tuah book documents. Observation techniques are used in data collection techniques, while the data analysis method in this study is the agih method with techniques for direct elements as a basic technique and advanced techniques in the form of sloping techniques. In Hikayat Hang Tuah there are three types of exocentric phrases (1) exocentric phrases directive with phrase-forming elements in the form of prepositions+nouns; (2) nondirective exocentric phrases with phrase-forming elements, namely particles/designations +adjectives and particles/word designations+nouns; and (3) connective exocentric phrases which form the phrase in the form of conjunctions+verbs. The diversity of linguistic elements in Hikayat Hang Tuah shows the manifestation of literary works as a manifestation of the richness of language.